A rubric to track the development of secondary pre-service and novice teachers' summative assessment literacy. Issue 2 (3rd April 2017) - Edwards, Frances
Abstract: Teachers require specialised assessment knowledge and skills in order to effectively assess student learning. These knowledge and skills develop over time through ongoing teacher learning and experiences. The first part of this paper presents a Summative Assessment Literacy Rubric (SALRubric) constructed to track the development of secondary science teachers' summative assessment literacy. The analytic rubric consists of 10 dimensions spread across three categories drawn from the literature and context-specific empirical evidence: knowledge of assessment, understanding the context for assessment, and recognising the impact of assessment. The second part of this paper applies the SALRubric in a case study to explore the development of summative assessment literacy of New Zealand secondary science pre-service and novice teachers. An increasing sophistication in these teachers' summative assessment literacy was evident over 20 months albeit in a nuanced manner for individual teachers. The rubric was a very useful tool for evaluating and documenting shifts in teachers' summative assessment literacy over time. Implications of the use of SALRubric are discussed in terms of summative assessment literacy practice and development.